2020
DOI: 10.3390/su13010315
|View full text |Cite
|
Sign up to set email alerts
|

Ecodesign—A Review of Reviews

Abstract: With the intent of summing up the past research on ecodesign and making it more accessible, we gather findings from 106 existing review articles in this field. Five research questions on terminology, evolution, barriers and success factors, methods and tools, and synergies, guide the clustering of the resulting 608 statements extracted from the reference. The quantitative analysis reveals that the number of review articles has been increasing over time. Furthermore, most statements originate from Europe, are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 89 publications
0
11
0
Order By: Relevance
“…GM is a strategic approach that includes processes and systems for operational improvement and environmental impact throughout the product's life cycle (Fernando & Uu, 2017;Machado et al, 2020). It represents many design-environment approaches often labeled as sustainable manufacturing, green production, sustainable production, clean manufacturing, environmentally responsible manufacturing, and environmentally conscious manufacturing, amongst others (Schäfer & Löwer, 2021). GM aims to integrate clean production processes that reduce the ecological effects of a product during its life cycle (Eltayeb et al, 2011;Al Khattab et al, 2015).…”
Section: Gm and Fpmentioning
confidence: 99%
“…GM is a strategic approach that includes processes and systems for operational improvement and environmental impact throughout the product's life cycle (Fernando & Uu, 2017;Machado et al, 2020). It represents many design-environment approaches often labeled as sustainable manufacturing, green production, sustainable production, clean manufacturing, environmentally responsible manufacturing, and environmentally conscious manufacturing, amongst others (Schäfer & Löwer, 2021). GM aims to integrate clean production processes that reduce the ecological effects of a product during its life cycle (Eltayeb et al, 2011;Al Khattab et al, 2015).…”
Section: Gm and Fpmentioning
confidence: 99%
“…However, there are already many reviews about sustainable design. While few have addressed all of the elements of sustainability, some have focused on social design (Corsini and Moultrie, 2021), green design (Durif et al, 2010) or eco-design (Sch€ afer and L€ ower, 2020). Few studies conducted on the concept of sustainable design include societal, environmental and economic aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Pigosso et al (2015) indicated that there is a growing interest in the development of eco-design tools and methods. In a recent analysis Schäfer and Löwer (2020) noted that the pressure on companies to adopt eco-design is also growing. Furthermore, there is the intention to generate tools for the early stages of the product development process (Jeswiet & Hauschild, 2005) and tools for industrial designers (Lindahl & Ekermann, 2013), among others.…”
Section: Introductionmentioning
confidence: 99%